Effect of Street Performance (Busking) on the Environmental Perception of Public Space - Ho, Robbie; Au, Wing Tung (Frontiers in Psychology, 2021)
This is the first experimental study testing the effect of street performance (aka busking) on the subjective environmental perception of public space. It is generally believed that street performance can enhance people’s experience of public space, but studies advocating such a view have not used a control group to explicitly verify the effect of street performance. In response to this methodological limitation, we conducted two studies using experimental design. Study 1 (N = 748) was an online computer-based study where research participants evaluated the extent to which the presence vs. absence of street performance could change their perception of public space. Study 2 (N = 162) was a between-group quasi-experiment in an actual public space where people physically present in the space evaluated the perception of the space with vs. without street performance. Overall, we found converging results that street performance could make public space more visitable, more restorative, and more preferable. The current findings not only fill in a gap in the literature on street performance, but they also inform the policy making and regulations of street performance.